Joint Ventures between Online Portals and News Publishers: Will they be an Alternative to Symbiosis? - Ryu, Min Ho; Park, Jieun; Kwak, Kyu Tae (MDPI, 2020)
Around the world, legacy news publishers are suffering from the deep decline of revenues and face the challenge of survival. As the situation continues, conflicts between online portal and news producers are also intensifying. Under these circumstances, Naver, the biggest internet portal in Korea, and several Korean news publishers have begun to seek a new breakthrough-media joint ventures. The joint venture between online portals and news publishers is a unique collaboration model that has not been found in other countries. This study investigates the motivation of the media joint ventures and evaluates the performance. To do this, the study suggests the sustainability of media joint ventures. This model consists of five major categories of media joint ventures' performances, based on their strategic, financial, learning, managerial, and social influence aspects. After conducting an in-depth interview of media joint ventures and a focus group interview with nine experts from the media industry and business scholarships, the study shows that the media joint ventures could be a new alternative for both portals and news publishers. However, there were some differences in the sustainability evaluation of the operating body of the joint venture and outside experts.